Cloning and Polymorphism of Disease Resistance SLC11A1 Gene in Pig (Sus scrofa): A Review - Devi, Bhanita; Laskar, S.; Borah, P.; Bharti, P. K. (International Journal of Livestock Research, 2018)
Infectious diseases are responsible for major economic losses in livestock production. Using disease resistant breeds is of considerable importance in livestock species. Solute carrier family 11member 1 (SLC11A1) which is also called as Natural Resistance-Associated Macrophage Protein1 (NRAMP1), is one of the most potent candidate genes conferring host’s genetic resistance to various antigenically different intracellular pathogens. The gene controls the exponential growth of the bacteria during the early phase of infection. SLC11A1 have been identified and cloned in pigs and it is strongly expressed on macrophages and neutrophils following stimulation with lipopolysaccharide. The present review discuss the localization, function and molecular techniques used to study the cloning and sequencing of SLC11A1 gene polymorphism in pigs by using Restriction Fragment Length Polymorphism (PCR-RFLP) and Single Strand Conformation Polymorphism (PCR-SSCP) methods as the SLC11A1 gene plays a very important role due to its association with resistance/ susceptibility to various intracellular pathogens in human as well as in livestock species.